Llama Llama holiday drama - Dewdney, Anna. (New York, N.Y., U.S.A. : Viking, 2010)
Llama Llama becomes overwhelmed as Christmas preparations progress, until his mother reminds him of the real gift the holiday brings.
Keywords: Stories in rhyme; Christmas -- Fiction; Mother and child -- Fiction; Llamas -- Fiction